Becoming Queensland - Haebich, Anna (State Library Queensland, 2009)
Background: Virtual exhibition created as Historian in Residence at State Library of Queensland (2008-2009), which provided active partnership in research and public outreach to MOU between SLQ and GU. Project linked directly with Q150 celebrations, contributed to SLQ and GU initiatives to promote public history and creativity in Queensland. Curatorial role: leading and collaborating with staff in SLQ Heritage Collections, Design, and Marketing to develop concept, themes, style and layout in digital format; research stories and images; support librarian contributions; design of virtual exhibition ; assist marketing program. Contribution: important creative contribution to public understanding of Queensland history grounded in intensive research, rigorous academic standards and designed to engage public and students with shared past. SLQ's firs exhibition produced entirely in digital format. Innovative in examining Queensland history as dynamic 'work in progress' and in how it weaves together stories and images about people, places, institutions and lifestyles that made the state special. Narratives move back and forth between bygone days and the present. Accompanying text explains why these stories are important in Queensland's history and why they were chosen from SLQ collections. Educational interactives included inform and engage users. The process was unique in involving librarians to suggest story topics along themes developed by Haebich who supported them in writing short panel texts explaining why they chose these topics. The curator provided additional historical and cultural context and links. Significance: SLQ marketed the exhibition widely as a significant contribution to its Q150 celebrations and remains as permanent resource on SLQ website. Haebich, SLQ librarians, teachers continue to use it for teaching and public presentations.